ALGUNOS DATOS HISTOLOGICOS SOBRE LAS ESTRUCTURAS NERVIOSAS DE LA PIA MADRE - RUIZ RAMIREZ, S; COSTERO, ISSAC CARLOS (Instituto Politécnico Nacional, CD MEXICO, DF, MEX, 1942)
A search was made for endamoebic cysts in 300 fecal samples From 238 E coli positives, 51 or 214% had supernucleate cysts; from 70 E histolytica positives, 3 or 43% had supernucleate cysts Those findings show the necessity of having in mind such ca
BOL INST ESTUD MED BIOL
Keywords: DATOS, HISTOLOGICOS, ESTRUCTURAS, NERVIOSAS, PIA, MADRE; CIENCIAS MEDICAS; MEDICINA INTERNA; NEUROLOGIA